2017
DOI: 10.1177/0956462417695995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the concurrent use of dolutegravir and metformin in human immunodeficiency virus-infected patients

Abstract: An analysis of the interaction between dolutegravir and metformin was conducted in the HIV ambulatory clinic setting. This was a multicenter, retrospective case series evaluating adult, HIV-infected patients concurrently prescribed dolutegravir and metformin. Historical electronic medical records were utilized to collect case-specific data. Laboratory parameters including serum creatinine (SCr), hemoglobin A1c (HgbA1c), plasma HIV RNA, CD4 cell count, and lactate were reviewed. Adverse drug reactions were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…DTG has an excellent profile in terms of drug interactions. Metformin constitutes one of the exceptions, with a significant increase in metformin levels when co-administered with DTG [60]. This should prompt clinicians to closely monitor lactic acidosis symptoms when prescribing both drugs and US Prescribing Information suggests limiting the total daily dose of metformin to 1000 mg.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…DTG has an excellent profile in terms of drug interactions. Metformin constitutes one of the exceptions, with a significant increase in metformin levels when co-administered with DTG [60]. This should prompt clinicians to closely monitor lactic acidosis symptoms when prescribing both drugs and US Prescribing Information suggests limiting the total daily dose of metformin to 1000 mg.…”
Section: Drug-drug Interactionsmentioning
confidence: 99%
“…Many studies, ranging from basic to clinical studies, have been conducted on metformin and its clinical applications in treating various diseases [37][38][39][40][41]. Recent reports suggest that metformin may have the therapeutic potential to treat liver injury [42,43], in addition to its efficacy in treating type 2 diabetes [44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that both BIC and DTG increased metformin plasma exposure in healthy adults and the dose adjustment of metformin is recommended to maintain optimal blood glucose control ( Song et al., 2016b ; Custodio et al., 2017 ). There were no severe adverse effects such as lactic acidosis reported when dolutegravir and metformin were co-prescribed to HIV patients but evaluating concurrent use of metformin and DTG case by case should still be considered ( Masich et al., 2017 ; Naccarato et al., 2017 ).…”
Section: Drug-drug Interactionsmentioning
confidence: 99%